FEATURES AND TECHNIQUES OF WRITTEN TRANSLATION - Ziyоtova Ra’no Utkir kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. This article is devoted to the specific features and techniques of written translation. Written translation is the transmission in writing of the text in the source language in the system and means of the target language. As a rule, the source text is also submitted in writing. Written translation, unlike oral translation, takes more time, and therefore, the translator has more time to process the source information and select translation techniques.